Role of corporate governance in thriving green innovation practices: A case of emerging economy - Unbreen Arif; Muhammad Bilal Ahmad; Aimun Khawaja (PLoS ONE, 2026)
In recent years the concept of green innovation has gained global attention in solving environmental issues and advancing sustainable development but opting for green innovation has always been challenging for firms due to the lack of incentives and negative externalities. Corporate governance refers to processes and systems to control the firm and play a crucial role in the decision-making process. The current study aims to explore the role of corporate governance in thriving dynamic capabilities of firms to adopt green practices to create competitive advantage, value and sustainable growth. The company-wise data of emerging economy were extracted from their financial and sustainability reports w.e.f 2014–2023 to analyze the nexus between corporate governance and green innovation practices. The empirical analysis was performed with the generalised method of moments (GMM) using stata and for text analysis python libraries were used to analyze governance mechanisms in thriving green innovation and its impact on financial performance. The results indicate that corporate governance has a significant influence on firm performance and green innovation mediates the relationship between corporate governance and firm performance. The result of the study will be useful for policymakers and stakeholders to implement good corporate governance practices to thrive for green innovation and to be competitive to earn sustainable earnings.